Tayma, Saudi-Arabien: Bauwerkserhaltung - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
In the frame of the multidisciplinary project at Tayma, significant architectural remains have been systematically treated by conservators based on the concept for conservation and restoration developed by the expedition. A large representative building which was in use from the Nabataean period to Late Antiquity as well as a residential building, both in the centre of the site, are currently under conservation. For the consolidation of walls, a modified mud mortar based exclusively on locally available materials has been used.